Evaluation of efficacy and safety of esmolol in treating patients with septic shock - Bin Hou, MM; Ke Cai, MM; Yue Li, MM; Chunfang Hu, MM; Xuehua Pu, MD (Medicine, 2022)
Abstract. Background:. In septic shock cases, tachycardia and a hyperdynamic hemodynamic profile are characteristics of the condition. It has been reported that using beta antagonist esmolol constitutes a form of treatment to reduce heart rate to improve diastolic filling time and elevate cardiac output, which reduces vasopressor support. Still, there are controversial results. Therefore, in this study, the primary objective is to perform a meta-analysis by systematically evaluating the efficiency and security of using esmolol to treat septic shocks. Methods:. A systematic literature search for relevant randomized controlled trials that report evaluations on the efficiency and safety of using esmolol to treat septic shock patients from their inception to February 2022 will be conducted in three databases containing publications in Chinese language (WanFang, Chinese BioMedical Literature Database, and China National Knowledge Infrastructure) and four databases containing English language publications (Cochrane Library, PubMed, Web of Science, and EMBASE). The screening of the relevant studies will be performed by a pair of authors independently, and the screening involves examining the title, abstract and full-text stages, data extraction, and bias risk assessment. The results are summarized through the fixed-effects and random-effects models, the respective models will be utilized for data pooling according to the heterogeneity of studies that will be included. Moreover, publication bias is assessed if more than ten studies are considered. Results:. The results are a high-quality synthesis of the most recent evidence for esmolol usage in septic shock treatment. Conclusion:. Up-to-date evidence will be provided through the results of this systematic review related to assessing the efficacy and safeness of esmolol usage in treating septic shock. Ethics and dissemination:. Ethical permissions are not required as prepublished data are used. OSF registration number:. DOI 10.17605/OSF.IO/SKEZ7